Presence of antigenic and specific heat shock protein(s) of shigella flexneri and shigella sonnei - A/P Parikrishnan, Hemavathy (2015)
Shigellosis caused by Shigella spp. is a public health concern in developing countries. Due to global emergence of drug resistance to Shigella spp., the choice of antimicrobial agents to treat shigellosis is limited. Current identification of this pathogen is by conventional culture method and biochemical tests, which takes about 2 to 7 days to produce result. Hence, there is a need for a rapid and reliable test that would allow rapid management of shigellosis infections. Development of a specific and sensitive diagnostic test requires discovery of biomarker(s), which does not cross react with other bacteria and are specific only to Shigella spp .Heat shock proteins (HSP) are proteins expressed in bacteria during stress environment and these proteins have potential as biomarker in diagnostic field. Thus the aim of this study is to detect the presence of HSPs and biomarker(s) in the outer membrane proteins (OMPs) of S. flexneri and S. sonnei. Protein profiles of OMPs from the ATCC strain and clinical isolate of S. flexneri and S. sonnei were demonstrated using the technique of Sodium Dodecyl Sulfate-Poly Acrylamide Gel Electrophoresis (SDS-PAGE). The OMPs profiles of S. flexneri and S. sonnei expressed at 37°C was compared with the profiles of 38.5°C and 40°C (temperature in patients with fever during shigellosis) to assess the effect of temperature on the expression of the OMPs. This study demonstrated that the expression level of OMPs of S. flexneri and S. sonnei varies with increasing temperatures. The protein electrophoretograms were subjected to Western blot using serum from patients infected with S. sonnei and S. flexneri as well other related infections. Result of this study demonstrated 11 antigenic bands were detected when probed with sera from patients with S. flexneri infection against both anti-human IgA and IgG isotypes. A total of 14 and 11 antigenic bands were obtained against anti-human IgA and IgG respectively when probed with sera from S. sonnei infection. All the antigenic bands were checked for cross reactivity using sera from patients infected with Salmonella spp., Enteropathogenic Escherichia coli, Salmonella Typhi, Aeromonas hydrophila and Campylobacter jejuni. Three protein bands (33.3, 43.8 and 100.3 kDa) of the S. sonnei and 2 protein bands (25.6 and 63.2 kDa) of the S. flexneri did not cross reacted with sera from other infections, suggesting that these proteins are specific biomarker for S. flexneri and S. sonnei. The identified HSPs showing prominent increased in expression were further identified by MALDI-ToF-ToF analysis. The HSPs of 18.4, 25.6 and 57.0 kDa in size from S. flexneri were identified as Dps, WrbA and PepA respectively. Whereas, the HSPs of 43.8 and 100.3 kDa in size from S. sonnei were identified as Pbp and AceE. The increased expression of these proteins probably is a mechanism of survival of the bacterium at higher temperatures in the host body and could be potential diagnostic biomarkers. Therefore these identified specific proteins for S. flexneri and S. sonnei can be used as biomarkers for development of diagnostic test which would allow rapid and accurate diagnosis of shigellosis to control the disease outbreak.